Ta’lîm Mahârah Al-Qirâ’ah Bistikhdâmi Wasîlati WhatsApp fî Al-Madrasah Al-Tsânawiyah Al-Hukûmiyah 6 Padang - Helendya Daynesty (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2021)
The learning process at the time Covid-19 must be implemented online. The use of media in learning is very important. The WhatsApp application was chosen to be used in this online learning. This study aims to obtain information about the planning of learning maharah qira’ah using WhatsApp and implementation and evaluation. The research subjects here are the teachers and students of Islamic junior high school of 6 Padang and the object under study is the use of the WhatsApp application in learning maharah qira’ah. This study used a qualitative research design. The instruments used in this study were observation, interviews and documentations. The result obtained are that the teacher prepares a learning plan before the lesson begins, and in the learning process the teacher used WhatsApp as a learning by using the features contained in the WhatsApp application both verbally and in writing by using the features in the WhatsApp application